DA’WAH IN THE QUR’AN (THEMATIC TAFSIR) - nirwana, andri (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
Submission of good information to others is a human dedication to the universe. All human beings created have a vision and mission of life, namely devotion to the Creator by doing good for all nature and everything, depending on the profession and the role of each. The problem in this article is that De Jure all Muslims are obliged to improve this nature with da'wah, but De Facto found very few Muslims who preach according to their respective professional roles and find a lot of challenges in delivering da'wah so as to make Muslims less concerned about da'wah efforts in this universe. Against this problem, researchers used the Hermeunetic method that focused on the text language of the Qur'an and its interpretation to increase the motivation of Muslims in carrying out da'wah activities according to their respective professions for the good of the world. The results of this study were found in the Qur'an to find a lot of motivation for preachers to gain success in their missionary endeavors in the world and in the hereafter. The benefits of the results of this study are to provide motivation for preachers to always be istiqamah in carrying out their da'wah efforts, for the glory of Islam on this earth.